Review on Recent Progress in Magnetic Nanoparticles: Synthesis, Characterization, and Diverse Applications - Ali, Arbab; Shah, Tufail; Ullah, Rehmat; Zhou, Pingfan; Guo, Manlin; Ovais, Muhammad; Tan, Zhiqiang; Rui, YuKui (Frontiers in Chemistry, 2021)
Diverse applications of nanomaterials have revolutionized various sectors in the society. In recent decade, especially the magnetic nanoparticles (MNPs) have gained enormous interest owing to their applications in areas such as, medicine, catalysis, agriculture, and environment. Controlled surface engineering for the design of multi-functional MNPs is vital for achieving desired application. MNPs have demonstrated great efficacy as thermoelectric materials, imaging agents, drug delivery vehicles and biosensors. In the present review we have first discussed the design and fabrication of MNPs, followed by their diverse applications. The comprehensive review not only provides the mechanistic insight into the synthesis, functionalization and application of MNPs but also outlines the limits and potential prospects.